Bread Business Development Strategy in Increasing Sales at Al Mumtaz Bread (Rotaz) - Nurlina H; Marosimy Millaty (Jurnal Dinamika Sosial Ekonomi, 2022)
Sweet bread producers can be found easily to fulfill the wishes of consumers who want sweet bread to be present in their daily life. The large number of sweet bread producers makes business competition increasingly fierce, so that the selection of the right strategy is needed to increase sales. This study aims to identify and describe the business strategy that must be carried out by the Rotaz business so that the business can develop and increase sales. The research was conducted at the Rotaz business owned by the Islamic Boarding School (BUMPES), Al Mumtaz Islamic Boarding School. The data sources were primary data and secondary data. Respondents to the questionnaire are management who are relatively understanding and interested in choosing Rotaz's marketing strategy and consumers who choose it by purposive sampling. The data analysis technique is the Analytical Hierarchy Process (AHP). The AHP stage is carried out by the steps of compiling a hierarchy and determining the priority of criteria with the stages of synthesizing, measuring consistency, calculating consistency index (CI), and calculating consistency ratio (CR). Based on the research results, it is known that from four criteria and three alternatives that have been determined, the best recommendation for Rotaz business development is to increase concentration on consumer behavior, followed by marketing and the lowest is advertising. Keywords : Analytical Hierarchy Process, bread, strategy